What we see : advancing the observations of Jane Jacobs - Goldsmith, Stephen Arthur, 1954-; Elizabeth, Lynne (New Village Press, 2010)
Leading thinkers offer fresh insight into the workings of vibrant, ecological, equitable communities and their economies.